Effect of dissolved oxygen and nitrogen on emission of N2O from rivers in China. (February 2015) - Wang, Jianing; Chen, Nengwang; Yan, Weijin; Wang, Bei; Yang, Libiao
Abstract: Six rivers from three watersheds in China were chosen to study the temporal and spatial variations in nitrous oxide (N2 O) concentrations and emissions in order to examine the link between N2 O production and dissolved oxygen (DO) and nitrogen levels. These rivers can generally be divided into two types: runoff rivers with significant natural and agricultural runoff, and urban rivers with significant urban effluents. The results showed that N2 O concentrations were 0.15–1.07 (mean 0.51) and 0.22–22.7 (mean 4.10) ug N L −1 in runoff rivers and an urban river, respectively. N2 O was oversaturated in almost all the rivers, suggesting that the rivers were sources of atmospheric N2 O. N2 O emissions in the urban river (range from 1.53 to 2453, mean 529 ug N m −2  h −1 ) were significantly higher than those in runoff rivers (range from 0.51 to 80.9, mean 18.0 ug N m −2  h −1 ). We found a significant positive correlation of N2 O production with NO 3 − (r 2  = 0.30, p < 0.001) and a negative correlation of N2 O production with DO concentrations (r 2  = 0.22, p < 0.001) in runoff rivers. Particularly, there existed a significant positive relationship (r 2  = 0.21, p < 0.001) between NH4 + and N2 O production in an urban river. By using stepwise regression analysis, we found N2 O production can be predicted by the dynamics of DO and N levels: for runoff rivers, NO 3 − and DO explained 47% variability in N2 O production, while for the urban river, NH 4 + and DO explained 64% variability in N2 O production. We suggest that the IPCC method to calculate N2 O emission factors should be revised in view of the importance of these multiple factors. Highlights: Demonstrate heterogeneous pattern of N2 O concentration and emission in various rivers. N2 O in urban river were significantly higher than those in agricultural runoff rivers. NO3 - and DO explaining 47% variability in N2 O production in runoff rivers. NH4 + and DO explaining 64% variability in N2 O production in urban rivers.